High risk factors for severe hand, foot and mouth disease: A multicenter retrospective survey in Anhui Province China, 2008-2009 - Jiahua Pan; Mingwu Chen; Xuzhong Zhang; Yulong Chen; Hui Liu; Wei Shen (Wolters Kluwer Medknow Publications, 2012)
Objectives: This study sought to determine the high risk factors for severe hand, foot, and mouth disease (HFMD). Materials and Methods: Retrospective 229 severe HFMD cases from four hospitals in FuYang, HeFei, and BoZhou (Anhui Provincial Hospital, Fuyang City People's Hospital, No. 2 People's Hospital of Fuyang and Bozhou city People's Hospital) in 2008-2009 were studied, with 140 mild HFMD cases in the same area. Using univariate and multivariate logistic regression analyses, the high risk factors of HFMD were identified by comparing clinical and laboratory findings between severe cases and mild cases. Results: There was a significant difference in age, total duration of fever, rate of respiratory and heart, shake of limbs, white blood cell count, blood sugar, and CK-MB between the two groups. Univariate logistic regression analysis showed that severe cases were associated with age (<3 years), withdrawnness and lethargy, shake of limbs, tachycardia, total leukocyte count (≥17×10 9 /l), blood sugar (≥7 mmol/l), and CK-MB (≥16 mmol/l). Furthermore, age (<3 years), withdrawnness, and lethargy, shake of limbs, WBC (≥17×10 9 /l), and CK-MB (≥16 mmol/l) were found to be high risk factors for severe cases after multivariate logistic regression analysis. Conclusions: Clinicians should give importance to these risk factors. Early recognition of children at risk and timely intervention is the key to reduce acute mortality and morbidity.